What risks and for whom? Argentina’s regulatory policies and global commercial interests in GMOs - Pellegrini, Pablo Ariel (2013)
Regulatory frameworks on genetically modified crops present several differences, according to the specific procedures they take to deal with what they consider to be risks. Some of these differences have been studied between the United States and Europe, but there are other scenarios and subjects that may also be involved. Argentina not only has one of the major land areas devoted to transgenic agriculture, but it also has one of the first regulatory agencies in the region. Nevertheless, its regulatory policies towards genetically modified organisms (GMOs) have several differences with some international regulatory policies, such as the precautionary approach, the Cartagena Protocol on Biosafety and the labeling of food derived from GM crops. In order to understand this position, we analyze the development and function of GMOs' regulatory framework in Argentina, comparing it with Europe and showing how commercial interests in agriculture may explain each regulatory approach.